Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Dalam Meningkatkan Motivasi Belajar Pada Mata Kuliah Bimbingan dan Konseling Mahasiswa PGSD - Musfirah Musfirah (Universitas Negeri Makassar, 2020)
This study aims to determine whether the application of the Two Stay Two Stray (TS-TS) cooperative learning method can increase Learning Motivation in the guidance and counseling course of PGSD campus V Parepare students at UNM. The research approach used in this research is qualitative. Type of classroom action research. The data analysis technique used qualitative data analysis which was analyzed descriptively. Data collection techniques using observation. This research consisted of two cycles, namely cycle I and cycle II. Based on the acquisition of the observation value in the first cycle, it was found that 65.69% of students' learning motivation in the guidance and counseling course was in a sufficient category. Meanwhile, the percentage of lecturers' success in teaching was 66.6% and it was in a sufficient category. In the second cycle student learning motivation in the guidance and counseling subject was 76.54% in the good category. In the aspect of the lecturer, data was obtained that the percentage of lecturers' success in teaching was 87.87% and was in a good category. So it can be concluded that the application of the cooperative learning model type two stay two strays (TSTS) can increase student motivation to learn in the guidance and counseling course of PGSD Campus V Parepare UNM students.